PROXY SERVER MAKING COMPUTER NETWORK USING LINUX UBUNTU 8.04 SERVER AS INTERNET - Udin Mahpudi; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2009)
Proxy server is a computer or program that can act as another computer to request the content from the Internet. Proxy Server acts as a gateway to the internet world for each client computer. A user interacts with the Internet via a proxy server will not know that a proxy server is handling requests are done. Web server that receives requests from the proxy server will interpret the request - these requests as if - if the request came directly from the client computer, instead of the proxy server.Proxy servers can also be used to secure private network that is connected to a public network (like internet). Proxy server has more functionality than a router that features packet filtering, proxy servers because it operates at a higher level and have a more comprehensive control of network access.